The Information System Project Profiles among Universities in Indonesia - A'ang Subiyakto; Abd. Rahman Ahlan; Mira Kartiwi; Nashrul Hakiem; Muhammad Qomarul Huda; Aries Susanto (Institute of Advanced Engineering and Science, 2018)
Information system (IS) utilizations may have been one of the determinant factors for the survival requirement of the higher education sector in Indonesia. Despite the IS projects have been conducted since the 1980s in this country, but many studies indicated that success of the projects seems like in the low level. This survey study was purposed to know the status of the IS project success among universities by involving the internal stakeholders. The higher education database of the Ministry of Research, Technology, and Higher Education (MRTHE) and the Association of Computing and Informatics Institutions Indonesia (ASCII-I) in the year 2015 were used for selecting around 1.230 respondents based on a purposive random sampling. The blended questionnaires were then distributed with almost 298 (±24%) responses. This paper presents five project profiles, including the aim, IS strategic plan availability, internal team involvement, budget allocation, and the success level of the projects.